Optimising marketing spend: return maximization and risk minimization in the marketing portfolio - Ryals, Lynette; Dias, Sam; Berger, Maya (Westburn Publishers, 2007)
In a world of limited resources, marketing managers tasked to deliver shareholder value face decisions about how to maximize the returns on their marketing portfolio. Risk is less often considered. In finance the picture is very different; financial portfolio management is concerned with both risk and returns. The central innovation in this paper is the application of modern portfolio theory (MPT) to the management of marketing portfolios in food retailing and in drinks manufacturing. The authors develop a model that calculates an efficient frontier of marketing portfolios that maximize overall return within certain risk constraints, first for a simple two-segment marketing world and then for a more realistic multi-segment portfolio. However, marketing portfolios differ from financial ones in the sense that the allocation of marketing spend affects the returns from the portfolio. Therefore, a second innovation, an extension of MPT to take account of marketing spend allocation decisions, has been developed. Using this model, marketers can determine the risk and the returns of marketing investments, helping them select an optimal portfolio. This would go some way to ensuring that marketing contributes to shareholder value creation, currently one of its major challenges.